The Regulatory Framework for Epidemic Control - A Comparative Study - Mohammed, Asst.Prof. Dr. Sangar D.; Mustafa, Hawree A. (Mitanni Journal of Humanitarian Sciences, 2023)
This study is based on the research in the duty of the administrative authorities through the means of administrative control and the achievement and protection of public health in society, as confirmed by international treaties and covenants and national legislation considering the right to health as one of the most important human rights, as these means are represented in the means possessed by the administrative bodies Legal, material and human, with the aim of preserving public health and combating epidemics. The administrative control bodies enjoy a sufficient and large amount of powers that ensure that they take whatever means and methods they deem appropriate to achieve their goal of preserving public health and combating epidemics.